Essays on ESL Reading and Writing - Normazla Ahmad Mahir (Universiti Sains Islam Malaysia, 2022)
The interesting feature of this collection of works is that it does not only include some of the common problems faced by many language learners but also some insightful ideas on teaching techniques in the ELT scenario in the country as well as the teaching of literature in small '1'. The writers have put forward intellectual discussion focusing on the topic given; hence instigating ideas for readers to explore new areas for research.